Support for Islamic Understanding from Families Information of Piety for The Millennial Generation - Abd. Basir; Abdul Wahab Syakhrani; Vani Wirawan; Arman Harahap; Gunawan Widjaja (Nazhruna: Jurnal Pendidikan Islam, 2021)
Guiding the younger generation in understanding Islam from the family informing the piety of the millennial generation is essential even though the government and society have established Islamic religious schools. To ascertain the extent to which Muslim families have carried out such guidance, we have obtained supporting data from various literature sources, including findings published in international journals that we have searched electronically on the Google Scholar application from the 2010 issue to the most recent 2021. Furthermore, our analysis process involves evaluating, coding, and critical interpretation under a phenomenological approach. During the reporting, we choose a descriptive analysis system. All of our data depend on secondary, considering that this study was carried out when Indonesia was implementing PPKM, namely the period of the national public movement restriction policy. After the process of discussing the results, we can summarize that the task of guidance and family responsibilities in children's education lies with parents in the family, including things such as the motivation or encouragement of love that animates the relationship between parents and children and the provision of motivation for moral obligations as the consequences of the position of parents to their offspring so that the hope that someday the children will become pious and pious children. Thus, these findings should be part of efforts to educate children in the millennial era.